2016
DOI: 10.1590/s1517-707620160002.0036
|View full text |Cite
|
Sign up to set email alerts
|

Materiais celulares vítreos obtidos via colagem de gel de uma emulsão de óleo vegetal

Abstract: RESUMOResíduos de vidro podem ser reutilizados para o desenvolvimento de materiais alternativos. Uma opção viá-vel são os materiais celulares para isolamentos térmicos já que, apresentando poros isolados, possuem baixa condutividade térmica, baixa densidade aparente e temperaturas de serviço mais altas que a dos materiais isolantes poliméricos. Neste trabalho, foi preparada uma suspensão aquosa com resíduos de vidro previamente moídos, Ágar-ágar (gelificante) e Emustab® (emulsificante), a qual foi adicionada d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Research using glass residues and banana leaves as pore forming agents showed that the addition of an organic agent decreased the apparent density of glass foam with the increase in residue (0.31 and 1.03 g.cm -3 ), consequently increasing its porosity (58.5 to 87.5%) 6 . Glass foams produced from bottle glass residues by the emulsification method using vegetable oil as a porogenic agent presented similar behavior, with porosity varying between 74, 85 and 93% for additions of 50, 70 and 90% oil, respectively 26 . Table 3 shows the mean pore size of the glass foams produced containing 5, 15, 30 and 45% (mass) of tobacco residue and fired at 850 and 900 ºC.…”
Section: Resultsmentioning
confidence: 92%
“…Research using glass residues and banana leaves as pore forming agents showed that the addition of an organic agent decreased the apparent density of glass foam with the increase in residue (0.31 and 1.03 g.cm -3 ), consequently increasing its porosity (58.5 to 87.5%) 6 . Glass foams produced from bottle glass residues by the emulsification method using vegetable oil as a porogenic agent presented similar behavior, with porosity varying between 74, 85 and 93% for additions of 50, 70 and 90% oil, respectively 26 . Table 3 shows the mean pore size of the glass foams produced containing 5, 15, 30 and 45% (mass) of tobacco residue and fired at 850 and 900 ºC.…”
Section: Resultsmentioning
confidence: 92%
“…Sua função é controlar o fluxo sanguíneo unidirecional do ventrículo esquerdo para a aorta, evitando o refluxo sanguíneo para o coração. Quando há calcificação nessa válvula tanto a abertura como fechamento podem ficar comprometidos, levando ao estreitamento da área valvar ou a regurgitação e insuficiência da válvula (Cesconeto, 2021).…”
Section: Introductionunclassified